Translational Potential of RNA Derived From Extracellular Vesicles in Multiple Myeloma - Reale, Antonia; Khong, Tiffany; Mithraprabhu, Sridurga; Spencer, Andrew (Frontiers in Oncology, 2021)
The cross-talk between tumour cells and stromal cells is a hallmark of multiple myeloma (MM), a blood cancer that still remains incurable despite increased knowledge of its biology and advances in its treatment. Extracellular vesicles (EVs) derived from both tumour and stromal cells have been shown to play an important role in mediating this cross-talk ultimately favouring MM progression and drug resistance. Furthermore, EVs and their content including RNA (EV-RNA) have been successfully isolated from blood and are being explored as liquid biomarkers in MM with the potential to improve diagnosis and monitoring modalities with a minimally-invasive and repeatable analysis, i.e. liquid biopsy. In this review, we describe both the role of EV-RNA in defining the biological features of MM and their potential translational relevance as liquid biomarkers, therapeutic targets and delivery systems. We also discuss the limitations and technical challenges related to the isolation and characterization of EVs and provide a perspective on the future of MM-derived EV-RNA in translational research.